Integrating technology into the preschool learning environment - Gegenava, Monica (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The role of technology in today's educational process is growing more and more. Integrating technology into preschool education is important so that children can develop digital skills from an early age and use them in the learning process. The use of technology in the preschool learning environment has many advantages. Interactive teaching methods promote child motivation and engagement, which is essential for early learning. Adaptive learning platforms that are tailored to a child's individual needs and interests effectively promote their holistic development. Practical examples of technologies in preschool education are diverse. Education apps and programs help develop various skills like math, language, science and more. Interactive whiteboards and tablets allow children to engage in the learning process interactively, which makes learning more interesting and attractive. Virtual reality and virtual expeditions allow children to gain new experiences, which contributes to their socio-emotional development. The role of educators in integrating technology is critical. Educators must be aware of best practices in the use of technology and have the ability to use it effectively. Training and professional development programs that help improve teachers' technology skills are important. Integrating technology into preschool education also faces certain challenges. One of the main difficulties is the high financial costs of technology implementation and the lack of resources. Distrust of technology by educators and parents is also a significant challenge. It is important to manage and balance screen time so that children do not lose time and interest in other activities. From the perspective of the future, new technologies and their potential impact on preschool education is an effective step. Directions for the development of innovative approaches and opportunities for their implementation are important for improving the quality of preschool education. Integrating technology into the preschool learning environment is a step forward for children's education. Its effective and correct use contributes to the multifaceted development of children and the formation of skills needed for the future.